2019
DOI: 10.5296/jbls.v10i2.14339
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of Polyporales from Bafut Forest, Cameroon and Their Importance to Rural Communities

Abstract: The polyporales are a large order of pore fungi within the Basidiomycota (Kingdom Fungi). They are mostly found on decay wood with some edible and medicinal species and others causing diseases of trees. In Cameroon, the knowledge on the phylogeny of polyporales is limited, their historical uses as food, medicine, source of income and the sociological impacts are apparently threatened due to slow ethnomycology research drive. The aim of this study was to identify and determine the phylogenetic relationship of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Microporus vernicipes belongs to the Polyporales family and distributes in the tropical and subtropical zone including Cameroon [11]. It has previously demonstrated that the water extract of Microporus vernicipes can have multiple activities such as antibacterial [12] and antioxidant [13] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Microporus vernicipes belongs to the Polyporales family and distributes in the tropical and subtropical zone including Cameroon [11]. It has previously demonstrated that the water extract of Microporus vernicipes can have multiple activities such as antibacterial [12] and antioxidant [13] effects.…”
Section: Introductionmentioning
confidence: 99%
“…A typical example is the polypore Microporus xanthopus a mushroom found in the wild in Nigeria and other tropical and temperate Countries. It is a medicinal mushroom and used as food in Cameroon but not in Nigeria (Kinge et al, 2019). Mushrooms are macro-fungi that possess bioactive compounds (secondary metabolites) that make them effective therapeutic agents in treating infections and various diseases (Niego et al, 2021;Adongbede and Aduralere, 2019).…”
mentioning
confidence: 99%